Genealogia da governamentalidade em Michel Foucault - Rone Eleandro dos Santos (2010)
The present dissertation aims to understand the processes through which the concept of governmentality was elaborated in the seminars Security, Territory, Population (1977-1978) and The Birth of the Biopolitics (1978-1979), offered by Michel Foucault in the Collège de France. Starting with the analysis of the different configurations of power - sovereign, disciplinary and biopower - we intended to elucidate the foucauldian research on other subjects as the conduction, the direction, the care and, mainly, the government of the others. In this manner, we analyze the different models of governmentality studied by Foucault: the archaic form of governmentality present in the old pastoral power; the modern governmental rationality that operated from the XVI to XVIII centuries; the liberal type conceived in middle of the XVIIIcentury and its neoliberal inflection operating until our days.